2010
DOI: 10.1007/s00198-010-1370-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute exercise on undercarboxylated osteocalcin in obese men

Abstract: This study reports that the reduction in serum glucose post-acute exercise (especially aerobic exercise) may be partly related to increased unOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 24 publications
(32 reference statements)
1
84
2
1
Order By: Relevance
“…In the subgroup with diabetes, the increased percentage of undercarboxylated osteocalcin was the main predictor of the reduction of glucose levels after exercise. These results suggested that improvement of glucose metabolism after exercise could be partly explained by the increase of undercarboxylated osteocalcin (45).…”
Section: Human Studies Involving Undercarboxylated Osteocalcinmentioning
confidence: 78%
“…In the subgroup with diabetes, the increased percentage of undercarboxylated osteocalcin was the main predictor of the reduction of glucose levels after exercise. These results suggested that improvement of glucose metabolism after exercise could be partly explained by the increase of undercarboxylated osteocalcin (45).…”
Section: Human Studies Involving Undercarboxylated Osteocalcinmentioning
confidence: 78%
“…Human interventions to increase osteocalcin serum levels have been tested indirectly. In a pilot study in obese patients submitted to either an aerobic or a power acute exercise (39), the reduction in serum glucose post-acute exercise at 2 h was correlated with the percentage change of uncarboxylated osteocalcin, especially in the aerobic program. In addition, a post hoc analysis of the PaTH study (PTH 1-84 vs alendronate) showed that higher increase in uncarboxylated osteocalcin at 3 month was associated with higher increase in adiponectin and greater decrease in body weight and fat mass at 1 year (40).…”
Section: European Journal Of Endocrinologymentioning
confidence: 97%
“…In non-diabetic adults, weight loss associated with diet and exercise also increased osteocalcin levels in parallel with a decrease in visceral fat and improved insulin sensitivity [50]. Interestingly, acute aerobic, but not power exercise could increase serum ucOC in obese individuals [51].…”
Section: Clinical Relevance Of the Osteocalcin-mediated Regulation Ofmentioning
confidence: 99%